Clausenidin induces caspase-dependent apoptosis in colon cancer. Issue 1 (December 2016) - Waziri, Peter; Abdullah, Rasedee; Yeap, Swee; Omar, Abdul; Kassim, Nur; Malami, Ibrahim; How, Chee; Etti, Imaobong; Abu, Mary
Abstract Background Clausena excavata Burm.f . is a shrub traditionally used to treat cancer patients in Asia. The main bioactive chemical components of the plant are alkaloids and coumarins. In this study, we isolated clausenidin from the roots ofC. excavata to determine its apoptotic effect on the colon cancer (HT-29) cell line. Method We examined the effect of clausenidin on cell viability, ROS generation, DNA fragmentation, mitochondrial membrane potential in HT-29 cells. Ultrastructural analysis was conducted for morphological evidence of apoptosis in the treated HT-29 cells. In addition, we also evaluated the effect of clausenidin treatment on the expression of caspase 3 and 9 genes and proteins in HT-29 cells. Result Clausenidin induced a G0/G1 cell cycle arrest in HT-29 cells with significant (p < 0.05) dose-dependent increase in apoptotic cell population. The DNA fragmentation assay also showed apoptotic features in the clausenidin-treated HT-29 cells. Clausenidin treatment had caused significant (p < 0.05) increases in the expression of caspase 9 protein and gene in HT-29 cells and mitochondrial ROS and mitochondrial membrane depolarization. The results suggest the involvement of the mitochondria in the caspase-dependent apoptosis in clausenidin-treated colon cancer cells. Conclusion Clausenidin induces a caspase-dependent apoptosis in colon cancers through the stimulation of the mitochondria. The study demonstrates the potential of clausenidin for use in the treatment of colon cancers.